Seronegative paraneoplastic limbic encephalitis associated with thymoma (2020)
Paraneoplastic limbic encephalitis is an autoimmune syndrome characterized by the acute or subacute onset of encephalopathy, memory loss, confusion, temporal lobe seizures, and behavioral and mood changes. Although most patients with paraneoplastic limbic encephalitis have antineuronal antibodies, advances in the field now permit the diagnosis without autoantibody test results. In this case illustrating the new diagnostic criteria, we report a 70-year-old woman who was brought to the emergency room after the acute onset of cognitive impairment, altered mental status, and choreoathetoid movements. Brain magnetic resonance imaging showed hyperintense signals in both temporal lobes, and a chest computed tomogram revealed a thymoma. Because the patient met current diagnostic criteria for autoimmune limbic encephalitis, we were able to start treatment before her antibody tests were processed. The patient received immunotherapy and her tumor was resected. Her choreoathetoid movements disappeared and her other neurologic symptoms improved. Her cerebrospinal fluid proved to be negative for paraneoplastic limbic encephalitis antibodies. Most but not all patients with paraneoplastic limbic encephalitis associated with thymoma have evidence of paraneoplastic antibodies. Prompt management of the underlying malignancy determines whether patients survive and may minimize future cognitive and functional impairment. Practicing neurologists and psychiatrists should be aware of this diagnosis.